Effects of environmental factors on vertical distribution of the eukaryotic plankton community in early summer in Danjiangkou Reservoir, China - Mai, Sijie; He, Yuxiao; Li, Weiguo; Zhao, Tongqian (Frontiers in Ecology and Evolution, 2023)
Eukaryotic plankton plays crucial roles in ecosystem processes, impacting aquatic ecosystem stability. This study focuses on Danjiangkou Reservoir, a canyon lake in central China, that acts as the water source of the Mid-route of the South-to-North Water Diversion Project. In this study, high-throughput 18S rDNA gene sequencing was employed to investigate eukaryotic plankton community at four water depths (0.5 m, 5 m, 10 m, and 20 m). The environmental factors including pH, water temperature (WT), nitrate nitrogen (NO3 --N), ammonia nitrogen (NH4 + -N), total nitrogen (TN), conductivity (Cond), and dissolved oxygen (DO) in reservoir areas were measured, and their correlations with abundance and diversity of eukaryotic plankton were analyzed. The results showed the presence of 122 genera of eukaryotic plankton from 38 phyla. Eukaryotic plankton communities were mainly composed of Eurytemora, Thermocyclops, Sinocalanus, Mesocyclops, and Cryptomonas.In particular, significant differences in the diversity of eukaryotic plankton communities were found in vertical distribution. The diversity and abundance of eukaryotic plankton communities in 7 sampling sites decreased with the increase of depth from 0.5 to 10 m, while the diversity and abundance of plankton communities increased at 20 m. RDA analysis indicated that pH, depth, WT, NH4 + -N, DO, Cond, and NO3 --N could influence the vertical distribution of the eukaryotic plankton community in the Danjiangkou Reservoir. Among these eukaryotic plankton, Eurytemora, Thermocyclops, and Volvox were negatively correlated with pH and WT and positively correlated with depth. This study revealed a novel perspective on the distribution of the eukaryotic plankton community in Danjiangkou Reservoir, particularly in terms of vertical variation, which will be helpful to comprehensively understand ecological processes and to further ensure the water quality safety in this canyon-style reservoir.